Understanding the Knowledge, Attitude, Practice and Intention regarding Abortion among Federal and Provincial Policymakers - Bajracharya, Madhabi; Gyawali, Nisha; Bhattarai, Tejaswee; Joshi, Shipra; Devkota, Jivan; Devkota, Bishnu; Rai, Jayashree; Tandukar, Samasti; Timilsina, Amit; Dangol, Deeb Shrestha (Journal of Nepal Health Research Council, 2024)
Background: For more than two decades abortion is legalized in Nepal, recognizing unsafe abortion as one of the leading but preventable cause of maternal morbidity and mortality. To safeguard safe abortion as women’s rights, several policies, guidelines, training manuals have been developed along with training human resources and increasing access to abortion services across Nepal. However, access to safe abortion services remains a challenge. Hence, to unravel the possible reasons behind these challenges, this study explored the knowledge, attitudes, practices and intentions of policymakers of Nepal towards abortion. Methods: Mixed methodology was used incorporating self-administered questionnaire for quantitative data collection and semi-structured interview guidelines to interview twenty local leaders from federal and provincial level, identified through purposive sampling. The ethical approval was taken from Nepal Health Research Council prior to data collection. After transcription and translation to English, Dedoose application was used for qualitative thematic analysis while the quantitative data was analysed using SPSS version. Results: 70% understand that international health and human rights frameworks support abortion. Also, a majority (85%) believe that policies limiting abortion access create negative attitudes toward abortion. All the participants mentioned that they possess a good knowledge of safe abortion services. Majority of the participants had good attitude, confident in advocating, and had positive intention towards safe abortion services. However, existing socio-cultural barriers, lack of awareness, legal barriers and maintaining privacy were identified challenges to seek safe abortion and related services. Conclusions: Despite strong positive intentions, policy implementation gaps and lack of accountability have resulted in poor awareness, access, and acceptability of abortion related services. Further budget allocation, safe abortion prioritization, continuous advocacy, integration of abortion in preservice curriculum and community engagement and awareness will bridge these gaps – to ensure equitable access to quality services including women and girls from marginalized community and adolescents. Keywords: Intention; knowledge; policy gaps; policymakers; safe abortion.